Challenges in strengthening Malaysia’s SDGs: insights from the all-party parliamentary group Malaysia (APPGM) impact evaluation. - Lee, Adrian Yuen Beng *; Maslisa, Zainuddin *; Mohd Firdaus, Mohd Anuar *; Nurul Hidayat, Ab Rahman; Tan, Raan Hann (UTHM, 2024)
Establishing the All-Party Parliamentary Group Malaysia (APPGM) on the Sustainable Development Goals (SDG) signals a robust national commitment to the United Nations Sustainable Development Goals (SDGs). Aligned with the comprehensive principle of “Leaving No One Behind” (LNOB), this initiative follows a structured, four-phased approach of issue identification, project design, implementation, and rigorous monitoring and impact assessment. Through a multi-stage evaluation process encompassing domains such as Deep, Clear, Wide, and High, the impact of these projects was assessed, with considerations for SDG understanding and gender aspects. To ensure effective SDG implementation at the grassroots level, APPGM-SDG appoints evaluation groups to impartially evaluate the effectiveness of solution project implementations across Malaysian parliamentary constituencies. In 2023, the Central One team evaluated solution projects in Kuala Lumpur, Negeri Sembilan, and Melaka. This paper examines the challenges encountered by beneficiaries, solution providers, and evaluation teams during the Impact Evaluation (IE) of 18 projects in the Central One region. Beneficiaries faced hurdles in accessing follow-up learning opportunities and managing marketing and resources. Solution providers struggled with managing human interactions, while evaluators dealt with issues in communication and navigation. Improving the evaluation process and incorporating Technical and Vocational Education and Training (TVET) is imperative to address the needs of all involved parties, which will lead to more effective and sustainable development outcomes in the Central One region.